Epstein–Barr Virus Infection and Gastric Cancer. Issue 20 (May 2015) - Chen, Xin-Zu; Chen, Hongda; Castro, Felipe A.; Hu, Jian-Kun; Brenner, Hermann; Derakhshan., Mohammad
<x xml:space="preserve">Abstract</x> Abstract Epstein–Barr virus (EBV) infection is found in a subset of gastric cancers. Previous reviews have exclusively focused on EBV-encoded small RNA (EBER) positivity in gastric cancer tissues, but a comprehensive evaluation of other type of studies is lacking. We searched the PubMed database up to September, 2014, and performed a systematic review. We considered studies comparing EBV nucleic acids positivity in gastric cancer tissue with positivity in either adjacent non-tumor tissue of cancer patients or non-tumor mucosa from healthy individuals, patients with benign gastric diseases, or deceased individuals. We also considered studies comparing EBV antibodies in serum from cancer patients and healthy controls. Selection of potentially eligible studies and data extraction were performed by 2 independent reviewers. Due to the heterogeneity of studies, we did not perform formal meta-analysis. Forty-seven studies (8069 cases and 1840 controls) were identified. EBER positivity determined by in situ hybridization (ISH) was significantly higher in cancer tissues (range 5.0%–17.9%) than in adjacent mucosa from the same patients or biopsies from all control groups (almost 0%). High EBV nuclear antigen-1 (EBNA-1) positivity by PCR was found in gastric cancer tissues, but most were not validated by ISH or adjusted for inflammatory severity and lymphocyte infiltration. Only 4 studies tested for EBV antibodies, with large variation in the seropositivities of different antibodies in both cases and controls, and did not find an association between EBV seropositivity and gastric cancer. In summary, tissue-based ISH methods strongly suggest an association between EBV infection and gastric cancer, but PCR method alone is invalid to confirm such association. Very limited evidence from serological studies and the lack of novel antibodies warrant further investigations to identify potential risk factors of EBV for gastric cancer.